Targeting the mTOR Pathway in Leukemia. Issue 8 (6th April 2016) - Dinner, Shira; Platanias, Leonidas C.
ABSTRACT: Optimal function of multiple intracellular signaling pathways is essential for normal regulation of cellular transcription, translation, growth, proliferation, and survival. Dysregulation or aberrant activation of such cascades can lead to inappropriate cell survival and abnormal cell proliferation in leukemia. Successful treatment of chronic myeloid leukemia (CML) with tyrosine kinase inhibitors targeting the BCR‐ABL fusion gene is a prime example of effectively inhibiting intracellular signaling cascades. However, even in these patients resistance can develop via emergence of mutations or feedback activation of other pathways that cause refractory disease. Constitutive activation of the phosphatidylinositol 3‐kinase (PI3K)/protein kinase B (Akt)/mammalian target of rapamycin (mTOR) signaling pathway has been observed in different types of leukemia, including CML, acute myeloid leukemia, and acute lymphoblastic leukemia. Abnormal mTOR activity may contribute to chemotherapy resistance, while it may also be effectively targeted via molecular means and/or development of specific pharmacological inhibitors. This review discusses the role of PI3K/Akt/mTOR dysre‐gulation in leukemia and summarizes the emergence of preliminary data for the development of novel therapeutic approaches. J. Cell. Biochem. 117: 1745–1752, 2016. © 2016 Wiley Periodicals, Inc. Abstract : Constitutive activation of the phosphatidylinositol 3‐kinase (PI3K)/protein kinase B (Akt)/mammalian target of rapamycin (mTOR) signaling pathway has been observed in different types of leukemia, including CML, acute myeloid leukemia, and acute lymphoblastic leukemia. Abnormal mTOR activity may contribute to chemotherapy resistance, while it may also be effectively targeted via molecular means and/or development of specific pharmacological inhibitors. This review discusses the role of PI3K/Akt/mTOR dysre‐gulation in leukemia and summarizes the emergence of preliminary data for the development of novel therapeutic approaches.